2011
DOI: 10.1108/14676371111148036
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Brazilian federal universities

Abstract: Sustainability has turned out to be a complex issue in the scope of Legal Sciences, in proportion as it directly impacts relationships in society, demanding constitutional interpretation from the perspective of subsidizing social conflicts. This imposes direct implications for these relations, such as the issues inherent in city planning. The aim of the present proposal is to promote the hermeneutic discussion of sustainability from the perspective of the Constitution of the Federative Republic of Brazil, focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…The analysis included the theoretical and empirical literature and examined how educational institutions are tied into this complex web of attaining SDGs at the continental level. Among other factors, the paper posits that acceleration of achievement of SDGs requires harmonised and well-coordinated efforts from educational institutions such as universities, which are leaders in cutting-edge research, to complementary horizontal and vertical institutions such as government ministries and other related institutions [21,30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis included the theoretical and empirical literature and examined how educational institutions are tied into this complex web of attaining SDGs at the continental level. Among other factors, the paper posits that acceleration of achievement of SDGs requires harmonised and well-coordinated efforts from educational institutions such as universities, which are leaders in cutting-edge research, to complementary horizontal and vertical institutions such as government ministries and other related institutions [21,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of developing countries, forty Brazilian universities representing 89% of offered programmes conducted exploratory research to map the emphasis given to the SDGs. The conclusion was that the involvement of SDGs in business administration programmes was slow and irregular, with only 13 (33%) of offered courses having some links to the subject [21]. These irregular results could be attributable to a lack of macro convergence, which is characteristic of many developing economies.…”
Section: Economic Perspectivesmentioning
confidence: 99%
“…The journals Sayed & Asmuss (2013) conducted a study at the University of Saskatchewan, Canada, where they identified five key campus areas for improving university sustainability performance: teaching, research, operations, governance, and community participation. Palma et al (2011) identified the number of sustainability-related subjects offered in bachelor's degree courses in Business Administration at Brazilian federal universities. The process of mapping the universities enlisted data from the Registry of Institutions of Higher Education of the National Institute of Studies and Educational Research (Instituto Nacional de Estudos e Pesquisas Educacionais -INEPE).…”
Section: Methodsmentioning
confidence: 99%
“…Despite initiatives such as this Steinmetz (2009) observed that environmental education in most higher education institutions (HEIs) is limited to isolated initiatives because of low awareness in educators and the lack of the theoretical, methodological and teaching skills needed. Celia Palma et al (2011) showed that the inclusion of new courses involving sustainability in business administration programs is still irregular and slow. Jabbour et al (2013) also analyzed business schools incorporating environmental management issues in their core activities through teaching, research, outreach and management.…”
Section: Introductionmentioning
confidence: 99%